2016
DOI: 10.1016/j.ihj.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

One-year outcomes of a BioMime™ Sirolimus-Eluting Coronary Stent System with a biodegradable polymer in all-comers coronary artery disease patients: The meriT-3 study

Abstract: REF/2016/07/011808.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 22 publications
1
13
0
2
Order By: Relevance
“…The BioMime™ (Meril Life Sciences Pvt. Ltd., Vapi, India) is an ultra-thin sirolimus-eluting coronary stent (SES) with an established preliminary safety and efficacy record in the previous meriT-1, meriT-2 and meriT-3 trials in treating single de novo and complex lesions [8][9][10] . In the present randomised study, we compared the safety and efficacy of the biodegradable polymer-coated BioMime SES with the XIENCE family (XIENCE V ® , PRIME ® or Xpedition ® ; Abbott Vascular, Santa Clara, CA, USA) of durable polymer-coated everolimus-eluting coronary stents (EES) in patients undergoing PCI with up to two de novo native coronary artery lesions.…”
Section: Introductionmentioning
confidence: 99%
“…The BioMime™ (Meril Life Sciences Pvt. Ltd., Vapi, India) is an ultra-thin sirolimus-eluting coronary stent (SES) with an established preliminary safety and efficacy record in the previous meriT-1, meriT-2 and meriT-3 trials in treating single de novo and complex lesions [8][9][10] . In the present randomised study, we compared the safety and efficacy of the biodegradable polymer-coated BioMime SES with the XIENCE family (XIENCE V ® , PRIME ® or Xpedition ® ; Abbott Vascular, Santa Clara, CA, USA) of durable polymer-coated everolimus-eluting coronary stents (EES) in patients undergoing PCI with up to two de novo native coronary artery lesions.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, all different Imported DES are considered as equally effective and it is the reason for grouping them together. Similarly, total event rates of Indigenous DES of this registry are same as in published reports 13 ,14. The limitations of this study include that not all DES are represented and there is relatively high proportion of Release R and Promus family of DES.…”
Section: Discussionmentioning
confidence: 60%
“…The BM shares with the well-studied BioMime™ DES technological characteristic (sirolimus elution, biodegradable polymeric carrier and ultrathin stent struts) associated with low late lumen loss and reduced hazard of thrombus formation in both studies [11][12][13][14][15] and meta-analyses [16,17]. The primary safety and efficacy trials meriT-1 [18] and meriT-2 [19] and, more recently, the observational post-marketing multisite registry meriT-3 [14] reported low rates of major adverse cardiovascular events (MACEs) and late stent thrombosis. Finally, the randomized meriT-5 trial [20] demonstrated that BM was non-inferior to the XIENCE DES at 9-month follow-up.…”
Section: Discussionmentioning
confidence: 89%